Implementasi Program Penghijauan Melalui Kegiatan Penanaman Pohon di Desa Kalikatir: Studi Partisipatif Mahasiswa KKN - Rachmad Sholeh; Angel Adinda Putri Utama; Achmad Dwi Aprillianto; Adimas Indra Putra; Amelia Zahro; Audriandra Risma Kurnia Salsabila; Fathur Rahiman Arif; Fifiana Anjika; Ilham Zakariya; Irma Matus Solikhah; Ivanda Syaikur Rochman; Lailatul Maghfiroh; M. Shieva Renjiro Alfathihah; Marthalia Al Fattah; Mela Dinda Eka Saputri; Melisa Christina Santoso; Mohammad Falah Yoga Aditta Putra; Mohammad Faisal Nur Alfian; Muhammad Arif Mustofa; Natalia Arta Nivia Saputri; Naufal Nur Arifiansyah; Nisaul Maghfiroh; Rangga Lesmana; Risquita Putri Diandra; Rois Dyaksa Abdul Fattah; Satifa Ajeng Listiyonigrum; Icha Cantika; Derry Annas Prakoso (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The greening program is an important effort to improve environmental quality and strengthen community awareness of ecological sustainability. This study aims to describe the implementation of tree-planting activities carried out by university students in Kalikatir Village through a participatory approach. The research employed a qualitative descriptive method, using observation, interviews, and documentation as data-collection techniques. The findings indicate that community participation plays a significant role in the success of the program, particularly in selecting planting locations, providing tools and support, and maintaining the planted trees. The greening activities have produced positive impacts, including increased vegetation cover, a cooler village environment, and stronger community awareness of the importance of green spaces. Moreover, collaboration between students and local residents has enhanced social cohesion and supported the sustainability of environmental initiatives. This study concludes that a participatory approach combined with a qualitative descriptive method is effective in understanding the dynamics of implementing greening programs at the village level.